MEASURING THE CUSTOMER SATISFACTION OF ECONOMIC CAPITALIS THEORY - Sumadi, Sumadi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
Profits earned by employers and wages earned workers essence is the price. The profit for the entrepreneur is the price he gets from the consumer, while the wage for the worker is the price that the employer must pay. Thus price is the driving force of production. From the above explanation, it can be deduced that the productive or productive activities of man in the view of Capitalism is a human sacrifice driven by material incentives. Consumer Behavior Theory studies how humans choose between the various options they face by utilizing the resources it has. The theory of rational consumer behavior in the conventional economic paradigm is based on the basic principles of utilitarianism. Initiated by Bentham who says that in general no one can know what is good for his own good except the person himself. Thus restrictions on individual freedom, either by other individuals or by the authorities, are evil and there must be a compelling reason to do so. Profits earned by employers and wages earned workers essence is the price. The profit for the entrepreneur is the price he gets from the consumer, while the wage for the worker is the price that the employer must pay. Thus price is the driving force of production. From the above explanation, it can be deduced that the productive or productive activities of man in the view of Capitalism is a human sacrifice driven by material incentives.